A study of equity financing modes for Islamic financial institutions in a shari'ah perspective - Sadique, Muhammad Abdurrahman (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2007)
This thesis analyses major areas related to implementation of the Islamic equity financing modes of mushārakah and muÌārabah by Islamic financial institutions from a Shari'ah perspective, with a view to highlighting important principles and aspects requiring review. It attempts to suggest possible measures for upgrading current practice in order to strengthen the shari'ah basis and realise the socioeconomic objectives of these modes. The research consists of a brief survey of the concept and regulations of shirkah and muÌārabah, and a detailed analysis of selected aspects related to four major areas of equity financing by Islamic banks, viz. capital, profit and loss sharing, equity investment accounts and project financing. Under capital in equity financing, the existence of capital at commencement, conversion of debt into capital, and involvement of commodities as capital are analysed. The Shari'ah theory pertaining to the nature of capital is examined in detail. The research shows that the current method for determining the profit sharing ratio in equity ventures based on the application of the rate of return on capital and the period of exposure needs revision. Two alternatives are proposed based on the capital and labour contributions of the partners. Stipulations affecting the functioning of the profit sharing ratio are scrutinised. The effect of withdrawal and period of investment on allocation of profit among investors in equity investment accounts is examined. The study highlights the need for a system for allocation of loss among investors. An alternative scheme for investment accounts is outlined. Important aspects of decreasing partnership and other equity structures for project financing are analysed. It is shown that adopting the equity basis could curb some negative aspects found in debt financing structures.